PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, OPINI AUDIT DAN REPUTASI KAP TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Fira Alya Putri (2021)
The Effect of Profitability, Firm Size, Auditor's Opinion and Reputation of Public Accounting Firm on Timeliness Reporting Financial Statement By Fira Alya Putri Abstract This purpose of this study to examine the effect of Profitability, Firm Size, Auditor's Opinion, Reputation of Public Accpunting Firm on Timeliness Reporting Financial Statement. In this study Logistic Regression is carried out with significance 5% on 39 sample of mining companies on the IDX during period 2017-2019. Profitability is measured by ROE, Firm Size is measured by ln asset total, Audit's Opinion and Reputation of Public Accpunting Firm are measured by dummy variable. This research showed that (1) Profitability has no significant effect on Timeliness Reporting Financial Statement, (2) Firm Size has no significant effect on Timeliness Reporting Financial Statement, (3) Auditor's Opinion has significant effect on Timeliness Reporting Financial Statement and (4) Reputation of Public Accounting Firm has significant effect on Timeliness Reporting Financial Statement.